1999
DOI: 10.1029/1998jd100050
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide emission from a Norway spruce forest floor

Abstract: Abstract. Although the available data on soil NO emission are increasing, only few measurements have been made in temperate forests. Emissions from these forests are generally low, but recent studies have shown that NO emission from N-affected forests can be much higher. In this study the emission of NO from the floor of a moderately N-affected Norway spruce forest in Denmark was measured using dynamic chambers during two seasons (April 1995 and September 1995). At the same time, fluxes of CO2 and NO2, soil wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 31 publications
(16 reference statements)
7
37
0
Order By: Relevance
“…35%), but the exchange of nitrogen oxides (NO, N 2 O and NO 2 ) has so far only been investigated in a few European forests. These studies in N-affected forests in Central (Butterbach-Bahl et al, 1997;van Dijk and Duyzer, 1999;Brumme and Beese, 1992;Gasche and Papen, 1999) and Northern Europe (Pilegaard et al, 1999;Skiba et al, 1998) have shown that European forests have a much higher NO and N 2 O emission than other temperate forests in the world (Williams et al, 1992;Castro et al, 1993). It has been suggested that the high emissions found in European forests are due to the high atmospheric N-input to these forests.…”
Section: Fig 1 Nofretete Field Stationsmentioning
confidence: 99%
See 2 more Smart Citations
“…35%), but the exchange of nitrogen oxides (NO, N 2 O and NO 2 ) has so far only been investigated in a few European forests. These studies in N-affected forests in Central (Butterbach-Bahl et al, 1997;van Dijk and Duyzer, 1999;Brumme and Beese, 1992;Gasche and Papen, 1999) and Northern Europe (Pilegaard et al, 1999;Skiba et al, 1998) have shown that European forests have a much higher NO and N 2 O emission than other temperate forests in the world (Williams et al, 1992;Castro et al, 1993). It has been suggested that the high emissions found in European forests are due to the high atmospheric N-input to these forests.…”
Section: Fig 1 Nofretete Field Stationsmentioning
confidence: 99%
“…Butterbach-Bahl et al, 1997;Pilegaard et al, 1999;van Dijk and Duyzer, 1999). NO was measured with dynamic chambers and the flux was estimated by comparing the steady-state concentration in the chamber with a reference measurement or by using the full mass balance equation (Altimir et al, 2002).…”
Section: Flux Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the three closest sites (A-C) 2 square automatically closing dynamic PTFE chambers (18 l) were installed for hourly NO, (NO x -NO) and O 3 flux measurements per site. The chamber system is described in detail by Pilegaard et al (1999). Two small fans stirred the air in each chamber.…”
Section: Site Description and Methodsmentioning
confidence: 99%
“…Nitric oxide in soil is produced through biological processes of nitrification and denitrification, as well as chemical decomposition of HNO 2 (Firestone and Davidson, 1989;Remde and Conrad, 1991;Conrad, 1996;Gödde and Conrad, 2000;Russow et al, 2009). Temperature, soil moisture, soil texture, fertilization and land-use have all been shown to be key factors controlling NO emission from soils (Gut et al, 1999Pilegaard et al, 1999;Venterea and Rolston, 2000;Venterea et al, 2005;Williams and Fehsenfeld, 1991;Yu et al, 2008). The approximate ranking of NO emission levels sources, viz.…”
Section: Introductionmentioning
confidence: 99%